2012
DOI: 10.1016/j.gr.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

First occurrence of a new Ocruranus-like helcionelloid mollusc from the lower Cambrian of East Gondwana

Abstract: A new cap-shaped mollusc, Emargimantus angulatus gen. et sp. nov. is described from the Arrowie Basin of South Australia. The new species is closely comparable to mollusc species from South China and North-East Greenland previously described under the generic name Ocruranus Liu, a genus recently reinterpreted as a multiplated, possibly polyplacophoran mollusc. Emargimantus is interpreted as a univalved helcionelloid mollusc and differs from Ocruranus in both morphology and function. Emargimantus angulatus repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Skovsted et al . (2012) established the genus Emargimantus to encompass a group of enigmatic orthoconic fossils that develop a high, erect shell with the subapical wall drawn out into an apron that bears a shallow median emargination. The morphologically similar Ocruranus trulliformis (Jiang, 1980), Ocruranus septentrionalis Peel & Skovsted, 2005, Ocruranus tunuensis Peel & Skovsted, 2005, and possibly Ocruranus sp.…”
Section: Systematic Palaeontologymentioning
confidence: 99%
See 2 more Smart Citations
“…Skovsted et al . (2012) established the genus Emargimantus to encompass a group of enigmatic orthoconic fossils that develop a high, erect shell with the subapical wall drawn out into an apron that bears a shallow median emargination. The morphologically similar Ocruranus trulliformis (Jiang, 1980), Ocruranus septentrionalis Peel & Skovsted, 2005, Ocruranus tunuensis Peel & Skovsted, 2005, and possibly Ocruranus sp.…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…in Peel & Skovsted (2005) were reassigned to Emargimantus , and tentatively reinterpreted as helcionelloid molluscs (Skovsted et al . 2012). In contrast, other shells referred to Ocruranus , with moderately high cap‐shaped shells and a distinctive upfolded subapical margin are likely to belong to a larger scleritome that consists of multiple skeletal elements such as Eohalobia Jiang, 1982 and some intermediate plates, and might represent a member of the chiton stem lineage (Vendrasco et al .…”
Section: Systematic Palaeontologymentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations: Max W¼maximum width; Max L¼maximum length; Max H¼maximum height; Rm W¼width of rostrum; Rm L¼length of rostrum; L to apex¼length to the apex. Skovsted et al (2012) noted the absence of additional multi-element components in association with the four Emargimantus species, which suggest that at least some taxa previously attributed to Ocruranus may have a closer affiliation with univalved helcionelloid mollusks. We demonstrate here that both shell morphotypes of Oikozetetes mounti n. sp.…”
mentioning
confidence: 87%
“…Records of Ocruranus from the Bastion Formation (Stage 4) of North-East Greenland by Peel and Skovsted (2005) were revisited by Vendrasco et al (2009) who suggested only tentative assignment to the genus. Skovsted et al (2012) transferred the Greenland species and Ocruranus trulliformis (Jiang, 1980) to Emargimantus Skovsted, Brock andTopper, 2012. Vendrasco et al (2009, text-fig. 2) considered that Ocruranus represented the tail plate in a polyplacophoran-like mollusk, in which interpretation the emarginate, shallowly concave subapical surface lies at the anterior (right in Fig.…”
Section: Family Uncertain Genusmentioning
confidence: 99%